Polymer Photovoltaic Cells with Rhenium Oxide as Anode Interlayer. - Jinyu Wei; Dongdong Bai; Liying Yang (PLoS ONE, 2015)
The effect of a new transition metal oxide, rhenium oxide (ReO3), on the performance of polymer solar cells based on regioregular poly(3-hexylthiophene) (P3HT) and methanofullerene [6,6]-phenyl C61-butyric acid methyl ester (PCBM) blend as buffer layer was investigated. The effect of the thickness of ReO3 layer on electrical characteristics of the polymer solar cells was studied. It is found that insertion of ReO3 interfacial layer results in the decreased performance for P3HT: PCBM based solar cells. In order to further explore the mechanism of the decreasing of the open-circuit voltage (Voc), the X-ray photoelectron spectroscopy (XPS) is used to investigate the ReO3 oxidation states. Kelvin Probe method showed that the work function of the ReO3 is estimated to be 5.13eV after thermal evaporation. The results indicated the fact that a portion of ReO3 decomposed during thermal evaporation process, resulting in the formation of a buffer layer with a lower work function. As a consequence, a higher energy barrier was generated between the ITO and the active layer.